TINDAK TUTUR EKSPRESIF DALAM LIRIK ALBUM SIALNYA, HIDUP HARUS TETAP BERJALAN KARYA BERNADYA DAN IMPLEMENTASINYA PADA PEMBELAJARAN MENULIS PUISI - Novia Katingal Maharani; Aceng Hasani; Erwin Salpa Riansi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to describe the forms of expressive speech acts in the lyrics of the album 'Sialnya, Hidup Harus Tetap Berjalan' by Bernadya and to implement the results of the analysis in writing poetry lessons in high school Indonesian language classes. This research uses a qualitative approach with a documentation study method. The overall research results found 90 data points, including 45 data points of complaint speech, 12 data points of criticism speech, 10 data points of blame speech, and 23 data points of praise speech. The research results can be implemented in the form of a teaching module for the material 'Berkarya dan Berkreasi melalui Puisi’ based on song lyrics. Utilizing song lyrics as a medium can be an interesting alternative and can solve the problems faced by students and teachers in poetry writing lessons. This finding contributes to the development of pragmatic studies and innovations in literature learning in schools.